Familial secundum atrial septal defect with dysrhythmia associated with web neck - Kılıç, Zübeyir; Uçar, Birsen; Baş, Ferruh; Dinleyici, Ener Çağrı; Sarı, Ersin (The Turkish Journal of Pediatrics, 2002)
Most cases of atrial septal defect occur sporadically, but a few families have the defect as a genetic abnormality. A family having familial type secundum atrial septal defect with dysrhythmia associated with web neck is reported. In this family, two female siblings aged 11 (Case 1) and 4 years (Case 2) and their father had secundum atrial septal defect. Case 1 presented with two year history of syncope attacks and Case 2 with easy fatigability since early childhood. Both sisters also had web neck as a solitary anomaly. Electrocardiograms revealed prolonged PR interval and right bundle-branch block in both cases. In Case 1 first-degree atrioventricular block and Mobitz type I and II block were observed in Holter monitoring. Echocardiographical examination showed secundum atrial septal defect in both sisters. A permanent pacemaker was implanted in Case 1, and then atrial septal defects in both patients were surgically repaired; no postoperative complaints were observed. The father had been diagnosed as having atrial septal defect when he was 35 years old, and first-degree atrioventricular block and atrial flutter developed after open heart surgery. In conclusion, the association of secundum atrial septal defect and prolongation of PR interval should be considered as familial occurrence of atrial septal defect. Identification of atrial septal defect in more than one family member should prompt clinical evaluation of all relatives.